# Using elementary transformations, find the inverse of each of the matrices, if it exists in Exercises 1 to 17.    Q10.    $\begin{bmatrix} 3 & -1\\ -4 & 2 \end{bmatrix}$

$A=\begin{bmatrix} 3 & -1\\ -4 & 2 \end{bmatrix}$

$A=IA$

$\Rightarrow$          $\begin{bmatrix} 3 & -1\\ -4 & 2 \end{bmatrix}$ $= \begin{bmatrix}1&0\\0&1 \end{bmatrix}A$

$R_2\rightarrow R_2+R_1$

$\Rightarrow$             $\begin{bmatrix} 3 & -1\\ -1 & 1 \end{bmatrix}$ $= \begin{bmatrix}1&0\\1&1 \end{bmatrix}A$

$\Rightarrow$          $R_1\rightarrow R_1+2R_2$

$\Rightarrow$         $\begin{bmatrix} 1 & 1\\ -1 & 1 \end{bmatrix}$ $= \begin{bmatrix}3&2\\1&1 \end{bmatrix}A$

$R_2\rightarrow R_2+R_1$

$\begin{bmatrix} 1 & 1\\ 0 & 2 \end{bmatrix}$ $= \begin{bmatrix}3&2\\4&3 \end{bmatrix}A$

$R_2\rightarrow \frac{R_2}{2}$

$\begin{bmatrix} 1 & 1\\ 0 & 1 \end{bmatrix}$ $= \begin{bmatrix}3&2\\2&\frac{3}{2} \end{bmatrix}A$

$R_1\rightarrow R_1-R_2$

$\begin{bmatrix} 1 & 0\\ 0 & 1 \end{bmatrix}$ $= \begin{bmatrix}1&\frac{1}{2}\\2&\frac{3}{2} \end{bmatrix}A$

$\therefore A^{-1}=$$\begin{bmatrix}1&\frac{1}{2}\\2&\frac{3}{2} \end{bmatrix}$.

Thus the inverse of A is obtained using elementary transformation.

Exams
Articles
Questions